General description of aviation notions in the English language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
Historical excursus into development of the concept “word” has been carried out, a few definitions of this notion have been presented, a general description of aviation notions in the English language has been offered in the given article. It has been proved using examples that certain semantic groups can be distinguished within general aviation English.
Keywords: word; lexical meaning; semantics; semantic groups; aviation notions